Toxoplasmosis as an uncommon finding in biliary brush cytology: Case series exploration - Shazima Sheereen; Mohnish Zulfikar Manva; Abdul Hakeem Attar; Shamama Sheereen; Namrata N Patil; Sabiha Mokashi Khan (Biomedical and Biotechnology Research Journal, 2023)
Background: The protozoan Toxoplasma gondii is the parasite that causes toxoplasmosis. In immunocompetent hosts, it typically has no symptoms. A common source of the infection is undercooked meat. It can also be transmitted through contact with cat excrement. The parasite can be transmitted to the fetus during pregnancy. Immunocompromised patients may experience symptoms in the brain, lymph nodes, heart, liver, eye, and inner ear. Molecular methods, histology, or serology are typically used to diagnose toxoplasma. These were the few instances of toxoplasmosis identified in biliary brush smears that we know of as per research literature. Methods: A 4-year study was carried out by the Saraswati Dhanwantari Dental College and Hospital, Post Graduate Research Institute, Parbhani, India, between March 1, 2019, and March 1, 2023. A study has located five cases of cytological slides related to toxoplasmosis in the biliary brush over time. Results: The study looked at five cases, all of which experienced fatigue or weakness as their most common symptom. Abdominal pain was present in three of the cases. All five cases showed an enlarged common bile duct (CBD) and intrahepatic bile radicles on the ultrasound abdomen. Contrast-enhanced computed tomography shows dilated CBD and common hepatic duct. The endoscopic retrograde cholangiopancreatography-guided biliary brushing Papanicolaou (PAP) smear cytology showed the presence of numerous tachyzoite forms of toxoplasma in an inflammatory background, and the biliary brush cytology diagnosis was confirmed to be toxoplasmosis in all five cases. Conclusion: One of the main causes of biliary strictures is parasites. In all biliary cytology samples that tested negative for malignant cells, other potential diseases or infestations must be checked out.